Encouraging 'returns', obstructing departures and constructing causal links The new creed of Euro-African migration management - (:unkn) unknown (My University, 2018)
The paper unravels the impact of semantic and legal shifts at different scales over the past two decades on the framing of irregular migration. Several key moments have marked Euro-African relations in the field migration. Through the decoding of political exchanges between African and European actors, this article shows the predominant objectives of migration policies. The first aims to encourage "returns" of migrants from Europe to Africa. The second seeks to dissuade potential African candidates from leaving (implied towards Europe), and the third presupposes that the returns of some migrants will make potential migrants renounce the journey. In order to prevent departures and to justify returns, new causal links appear in speeches. There is here an idea of an archetypal model linking returns and deterrents. This binary justification of a presupposed causality between returns and departures is questionable however because evidence shows that returns will not necessarily have the expected deterrent effect. Nevertheless, the migration and development nexus has gradually come to complement the migration and security nexus. At different scales and through semantic and legal shifts, emigration has been framed as a “problem” then as a “crime” in the dominant policy discourse. Through the design and implementation of departure deterrence programmes, actors from NGOs, international organisations, political institutions and the media are strengthening the controversial notion of "illegal emigration" which, gradually, has become a new resource in the field of migration management.
Keywords: African Research